Data mining for business analytics : concepts, techniques, and applications in Microsoft Office Excel with XLMiner /: concepts, techniques, and applications in Microsoft Office Excel with XLMiner. (2016) - Shmueli, Galit, 1971-; Patel, Nitin R (Nitin Ratilal); Bruce, Peter C, 1953-
No abstract available